Identification of Surrogate Biomarkers for the Prediction of Patients at Risk of Low Macular Pigment in Type 2 Diabetes. (2nd December 2019) - Scanlon, Grainne; McCartney, Daniel; Butler, John S; Loskutova, Ekaterina; Loughman, James
ABSTRACT: Purpose : This cross-sectional study compared macular pigment (MP) levels among persons with Type 2 diabetes relative to healthy controls. Additionally, a range of behavioral, anthropometric, clinical and serum measures were explored as possible predictors of low MP optical density (MPOD) in diabetes. Methods : Two health status groups; Group 1: Type 2 diabetes (n = 188), and Group 2: Healthy controls (n = 2, 594) completed a full MP assessment using customized heterochromatic flicker photometry, as part of The Irish Longitudinal Study on Aging (TILDA). Clinical [blood pressure; cataract status; MPOD] and anthropometric [waist (cm); weight (kg); hip (cm)] measurements were taken, and a blood sample drawn for analysis of serum biomarkers [lipoproteins; inflammatory markers (C reactive protein and vitamin-D)]. Results : One-way ANOVA revealed lower MPOD in subjects with Type 2 diabetes relative to controls ( p = .047). Amongst participants with diabetes, those with low serum vitamin D (≤50 nmol/L) had significantly lower mean MPOD compared to those with sufficient serum vitamin D levels >50 nmol/L (0.173(0.148) vs. 0.226(0.145); p = .006). Concomitantly, MP was significantly lower in diabetes participants with raised serum triglyceride (TG) to high density lipoprotein (HDL) ratio (TG/HDL); values >1.74 mmol/L (0.172 (0.140) vs 0.215 (0.152); p = .039). Body mass index, waist-to-height ratio and waist circumference, were all significantly negatively correlated with MPOD (Pearson's correlation, p < .05 for all). Significant correlates of MPOD in the multivariate regression model included smoking, cataract, and vitamin D, which collectively contributed 18.5% of the overall variability in MPOD status amongst participants with Type 2 diabetes. Conclusions : This study provides additional evidence that low MP may indeed be a feature of Type 2 diabetes, and further identifies smoking, cataract and vitamin D status as plausible predictors of low MPOD amongst persons with Type 2 diabetes.